Peningkatan Hasil Belajar Dengan Model PBL tema Manusia Makhluk Pribadi Kelas X SMKN 2 Nangabulik - Marsianus Laki Pakae (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
In preliminary observation at SMK Negeri 2 Nanga Bulik, researcher found that learning outcomes by Catholic students in class X on the theme Human Beings as Personals was not optimal. Therefore this research aims to: 1. Improve the learning outcomes of class X students of SMKN 2 Nanga Bulik with the theme Human Beings as Personals. 2. Improving students' ability to apply moral elements to humans (P5). Learning is done with the PBL method. The results of the study: in cycle I, only 11.1% including the proficient category, the competent category 55.56%, the proper category 33.3%. Whereas in cycle II, students who reached the proficient category reached 67%, the competent category 22% and the feasible category 11%. Observational data related to the application of the P5 indicator that has been determined by the researchers,on average, has increased by 22%. Thus it can be concluded that the application of the PBL model contributes positively to improving student learning outcomes in class X SMKN 2 NangaBulik on the theme of Human Beings as Personals. It is suggested to teachers and schools to consider using the PBL model in learning to improve the quality of learning and student learning outcomes in the future.